Microstructure Evolution by Thermomechanical Processing in the Fe-10Al-12V Superalloy - Ferreirós, Pedro Antonio (2023)
Nowadays, great efforts are being made to develop bcc-superalloys for medium- andhigh-temperature applications. However, the high brittle-to-ductile transition temperatures (BDTT)have restricted their application. Therefore, designing hot-processing routes to obtain a refinedgrain in these new superalloys is required. Particularly in the Fe-10Al-12V (at%) alloy, we haverecently tested the BDTT shifting and, using physical models, it was indicated that a combination ofL21-precipitate sizes with small grain sizes could shift the BDTT below room temperature. Here, wewill present the study that allowed us to design the processing route for grain refinement in the testedsuperalloy. Molds of different geometry and with metallic and sand walls were used to test twodifferent types of casting. Carbide conditioning treatments for improving the sizes and distributionwere studied. The recrystallization process was explored first by hot rolling and post-annealing instepped geometry samples with two different columnar grain orientations. Finally, we analyzedthe grain microstructure obtained along a hot processing route consisting of carbide conditioningtreatment, forging into a squared bar, and hot rolling up to a 2.8 mm thickness strip.